Kajian pertumbuhan beberapa jenis ikan di perairan pesisir Kabupaten Kutai Timur: Growth study of several fish species in coastal of East Kutai Regency - Muhammad Syahrir R. (Jurnal Ilmu Perikanan Tropis Nusantara (Nusantara Tropical Fisheries Science Journal), 2022)
The status of fish populations is needed to properly manage these resources in order to maintain its sustainability. This study aims to examine the growth factor of some fish caught by trawl in East Kutai Regency include the length and weight relationships, condition factor, the alleged growth, Gonadal Development Level, gonadal Somatic index, and fecundity. The research was conducted in the sub-district of Kaliorang, Sangkulirang and Sandaran of East Kutai regency, East Kalimantan. Collection and measurement were conducted over a period of three months. Allometric growth patterns are found in gerot-gerot, niko-niko, teri, senangin, gulamah, bulu ayam dan lampa-lampa, while Isometric growth patterns found in puput. Highest condition factor found in gulamah with the value of 1.02 and the lowest value was found in the gerot gerot with value 0.083. The collected fish length growth equation was senangin. The Regression equation for growth length i.e. senangin Lt = 180,8 (1-e-1,7(t+1,25)), puput Lt = 221,5 (1-e-0,88(t+0,88)), and bulu ayam Lt = 200,55 (1-e-0,7(t+0,95)).